Los juegos motores como alternativa didáctica para mejorar el desarrollo motor en los niños de tercer año de educación básica de la Escuela Blanca Villamarín Ortíz, cantón Montalvo Parroquia La Esmeralda, en el periodo 2022 -2023 - Castro Tuarez, Eliana Isabel (2022)
The present case study was based on the theme: Motor games as a didactic alternative to improve motor development in children in the third year of Basic Education at the "Blanca Villamarin Ortiz" School, Montalvo Canton, La Esmeralda Parish. A Test Evanm, was carried out as an evaluation of the children, taking into account motor development based on the following parameters: balance, running, posture control. The study population was 10 students and the surveys were applied to the teachers, the research proposed a qualitative and quantitative research approach because the data was processed with the use of statistics through tables and graphs. It was found that the majority of children had shortcomings when performing the proposed exercises, but after the corrections given by the evaluator they managed to execute very easily, realizing that teachers do not use games as a means of learning in activities, for this reason We can affirm that through play, children can effectively develop their skills and awaken their interest in learning. This work is very important since it recommends a suitable game system to teachers, which will allow them to perfect motor development in children and above all, it will be very fun and significant in learning.